Estado da arte de scaffolds de TPU - Sobczak, Rafael dos Reis (Universidade Federal de São Carlos, 2025)
Due to their biocompatibility, bioresorbability, mechanical properties, and versatility in shaping, thermoplastic polyurethanes appear to be remarkable candidates for scaffold applications. In this context, this undergraduate thesis explores this polymer in depth, from the formation of the urethane group through the reaction between isocyanate and hydroxyl groups, to the polymerization of polyurethane, which may occur in one or two steps, and how its biphasic morphology of hard and soft domains primarily governs its mechanical properties. Furthermore, it defines the purpose of scaffolds, which is to mimic the extracellular matrix in order to promote the regeneration of damaged tissues. To achieve this, scaffolds must be biocompatible, biodegradable at rates compatible with the target tissue, and must also possess suitable mechanical properties and architecture. The latter is defined by the scaffold’s conformation, which involves many techniques and can be categorized into methods using porogenic agents, additive manufacturing, and fiber-based techniques. Thermoplastic polyurethane can be bioresorbable when the correct raw materials are used, degrading mainly through hydrolysis and generating non-toxic byproducts. Its mechanical properties are shown to be very similar to those of soft tissues. Thus, its main applications are in cardiovascular, musculoskeletal, and nervous tissue engineering. As a synthetic scaffold material, studies are being conducted to improve cell adhesion, for instance, through the use of peptides. Another research direction aims to make this polymer conductive, by incorporating conductive fillers or mechanically blending it with conductive polymers. Finally, this work also highlights gaps in the literature, such as the use of this material for cartilage regeneration, which remains poorly documented.
State of the art of TPU scaffolds
Keywords: Poliuretano termoplástico; Engenharia de Tecidos; Scaffold; Matriz extracelular; Thermoplastic polyurethane; Tissue engineering; Extracellular matrix; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS